Physicochemical Properties and Sensory Evaluation of Rice Paper Incorporated with Jackfruit Seed Flour - Wan Nur Izzah Wan Azizi,; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2024)
The trend of people seeking healthy meal options is evident in the food industry, prompting manufacturers of rice paper incorporated with jackfruit seeds to rapidly introduce new ingredients for preparing healthy meals. Jackfruit seeds flour, recognized for its high protein content, holds the potential to enhance the nutritional value of rice paper while mitigating its stickiness. In this study, the best formulation with various mixture proportions of ingredients for formulating rice paperincorporated with jackfruit seeds, including jackfruit seeds flour (JSF), rice flour (RF), and tapioca flour (TF), was determined using a simplex lattice mixture design method. The sensory characteristics and physicochemical properties (moisture content, protein content, texture, and color) of rice paper incorporated with jackfruit seeds samples were evaluated to identify the best formulation for comparison with control and commercial rice paper samples. Among seven formulations, three successfully maintained texture while the sensory evaluation revealed that panelists accepted all three rice paper incorporated with jackfruit seeds samples, with sensory scores ranging from 6 to 7. Formulation 2, comprising 33% rice flour, 33% tapiocaflour, and 33% jackfruit seeds flour, was identified as the most acceptable formulation, displaying 9.10 ± 0.31% moisture content, 2.27 g/100g protein content, and 0.94 ± 0.0mm thickness. The increase in jackfruit seeds flour in rice paper samples resulted in higher L*, a*, and b* values. Jackfruit seeds add nutritional value, specifically protein, to rice paper. Therefore, rice paper incorporated with jackfruit seeds represents a new healthy meal option with highly acceptable sensory and physicochemical properties.